2007
DOI: 10.1002/jts.20278
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress and depression symptoms in soldiers returning from combat operations in Iraq and Afghanistan

Abstract: The purpose of the present research was to identify rates of posttraumatic stress and depressive symptoms in soldiers returning from war. During reintegration training, U.S. Army soldiers, who recently returned from a 12-month deployment to either Iraq (Operation Iraqi Freedom, n = 2,275) or Afghanistan (Operation Enduring Freedom, n = 1,814), completed study materials. Surveys assessed self-reported levels of depression, posttraumatic stress, and life satisfaction. Results indicated that approximately 44% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
150
3
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(164 citation statements)
references
References 18 publications
10
150
3
1
Order By: Relevance
“…An earlier review (Tanielian and Jaycox, 2008) identified 11 studies that reported rates of depression among active-duty service members serving in OEF or OIF, ranging from 5 percent (Hoge, Auchterlonie and Milliken, 2006;Kolkow et al, 2007;MHAT-II, 2005) to 37 percent (Lapierre, Schwegler, and Labauve, 2007). Correlates of depression in the 11 studies included having a hospitalization during deployment or other physical problems; being female, under 25 years of age, nonwhite, or junior enlisted; and deployment intensity (i.e., level of combat, two or more deployments, deployment for more than six months) (Tanielian and Jaycox, 2008).…”
Section: Ptsd and Depression Among Service Membersmentioning
confidence: 99%
“…An earlier review (Tanielian and Jaycox, 2008) identified 11 studies that reported rates of depression among active-duty service members serving in OEF or OIF, ranging from 5 percent (Hoge, Auchterlonie and Milliken, 2006;Kolkow et al, 2007;MHAT-II, 2005) to 37 percent (Lapierre, Schwegler, and Labauve, 2007). Correlates of depression in the 11 studies included having a hospitalization during deployment or other physical problems; being female, under 25 years of age, nonwhite, or junior enlisted; and deployment intensity (i.e., level of combat, two or more deployments, deployment for more than six months) (Tanielian and Jaycox, 2008).…”
Section: Ptsd and Depression Among Service Membersmentioning
confidence: 99%
“…Some of these researchers failed to find gender differences in mental health problems occurring postdeployment, [7][8][9][10][11] but a few studies have found a higher incidence of PTSD in females returning from deployment compared with males, 12,13 who appear to have more substance abuse problems. 11 In some of these studies, female service members were also more likely than men to screen positive for depression.…”
mentioning
confidence: 99%
“…11 In some of these studies, female service members were also more likely than men to screen positive for depression. 7,8,11,[13][14][15] Greater psychologic morbidity has been seen in deployed military HCPs, explained by poorer group cohesion and traumatic military medical and postdeployment experiences. 16 Returning HCPs did not think that people understood what they had been through during deployment and felt unsupported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Given that U.S. soldiers are currently deployed for 15-month rotations, exposure to potentially traumatic events is lengthy, and traumatic stress symptoms may be more likely (9). Shortly after redeployment, approximately 44% of service members reported clinically significant depressive and/or posttraumatic stress symptoms (9).…”
mentioning
confidence: 99%